Inverted Wedding Cake Growth Operated by the Ehrlich–Schwoebel Barrier in Two‐Dimensional Nanocrystal Evolution. (6th January 2016) - Yin, Xin; Geng, Dalong; Wang, Xudong
Abstract: Wedding cake growth is a layer‐by‐layer growth model commonly observed in epitaxial growth of metal films, featured by repeated nucleation of new atomic layers on the topmost surface owing to the confinement of the Ehrlich–Schwoebel (ES) barrier. Herein, we report an inverted wedding cake growth phenomenon observed in two‐dimensional nanostructure evolution. Through a dynamically controlled vapor–solid deposition process of ZnO, a unique basin‐shaped crown was formed on the tip of each nanowire, featured with concentric steps. The atomic steps were nucleated along the edge and propagated toward the center. This is an opposite growth behavior compared to the conventional wedding cake growth, and is thus denoted as inverted wedding cake growth. Through the relation between the crown expansion rate and the temperature, the ES barrier of ZnO was determined to be 0.88 eV. The discovery of inverted wedding cake growth provided insight into the developing nanostructure growth mechanisms.